Pluripotent stem cells escape from senescence-associated DNA methylation changes - Koch, Carmen M.; Reck, Kristina; Shao, Kaifeng; Lin, Qiong; Joussen, Sylvia; Ziegler, Patrick; Walenda, Gudrun; Drescher, Wolf; Opalka, Bertram; May, Tobias; Brümmendorf, Tim; Zenke, Martin; et al. (Genome Research, 2013)
Pluripotent stem cells evade replicative senescence, whereas other primary cells lose their proliferation and differentiation potential after a limited number of cell divisions, and this is accompanied by specific senescence-associated DNA methylation (SA-DNAm) changes. Here, we investigate SA-DNAm changes in mesenchymal stromal cells (MSC) upon long-term culture, irradiation-induced senescence, immortalization, and reprogramming into induced pluripotent stem cells (iPSC) using high-density HumanMethylation450 BeadChips. SA-DNAm changes are highly reproducible and they are enriched in intergenic and nonpromoter regions of developmental genes. Furthermore, SA-hypomethylation in particular appears to be associated with H3K9me3, H3K27me3, and Polycomb-group 2 target genes. We demonstrate that ionizing irradiation, although associated with a senescence phenotype, does not affect SA-DNAm. Furthermore, overexpression of the catalytic subunit of the human telomerase (TERT) or conditional immortalization with a doxycycline-inducible system (TERT and SV40-TAg) result in telomere extension, but do not prevent SA-DNAm. In contrast, we demonstrate that reprogramming into iPSC prevents almost the entire set of SA-DNAm changes. Our results indicate that long-term culture is associated with an epigenetically controlled process that stalls cells in a particular functional state, whereas irradiation-induced senescence and immortalization are not causally related to this process. Absence of SA-DNAm in pluripotent cells may play a central role for their escape from cellular senescence.